SYNCRETISM AND POLYFUNCTIONALITY OF FORMS OF THE VOICES IN LANGUAGES IN DIFFERENT SYSTEMS (Scientific journal of the Fergana State University, 2023)
In this article interpretations, types, functional and stylistic properties of the category of voice, which is one the most disputable grammatical categories are studied in agglutinative and inflective languages. The syncretic characteristics and polyfunctional aspects of voice forms are analysed in the material of Uzbek and English languages.